SYNTHESIS OF 8-SUSBTITUTED-3,4-DIHYDRO-6-METHYL-4- PHENYLIMIDAZO [1,5-b][1,2,4]TRIAZIN-2(8H)-ONE DERIVATIVES AS NOVEL ANTIMICROBIAL AGENTS - A A BARVKAR,; S D SAWANT, (International Journal of Pharma and Bio Sciences, 2013)
A series of new 6-methyl-3,4-dihydroimidazo[1,5-b][1,2,4]triazin-2(8H)-one derivatives have been synthesized with the initial reaction of various aromatic aldehydes and N-acetylglycine in acetic anhydride and anhydrous sodium acetate by Erlenmeyer-Azlactone synthesis to give oxazol-5(4H)-one derivatives which on reaction with substituted phenylhydrazine in dry benzene gave 1H-imidazol-5(4H)-one and lastly condensation with chloroacetamide in N,N-dimethylformamide gave final compounds. All synthesized compounds were characterized by FT-IR, 1H NMR, 13C NMR, LC-MS and HPTLC etc and are well supported by spectroscopic data. These novel compounds are investigated for their in vitro antimicrobial activity using zone of inhibition using cup plate method. The antibacterial activities were compared with standard drug such as ciprofloxacin and antifungal drug such as cotrimazole at concentration of 250, 500 and 750 µg/L. Synthesized analogues showed favorable antimicrobial effect.